2015
DOI: 10.1098/rspb.2014.2161
|View full text |Cite
|
Sign up to set email alerts
|

How much does nasal cavity morphology matter? Patterns and rates of olfactory airflow in phyllostomid bats

Abstract: The morphology of the nasal cavity in mammals with a good sense of smell includes features that are thought to improve olfactory airflow, such as a dorsal conduit that delivers odours quickly to the olfactory mucosa, an enlarged olfactory recess at the back of the airway, and a clear separation of the olfactory and respiratory regions of the nose. The link between these features and having a good sense of smell has been established by functional examinations of a handful of distantly related mammalian species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…The architecture of the turbinals and floor of the nasal capsule determines whether orthonasal and/or retronasal air currents pass directly over olfactory epithelium. Turbinals are highly variable between mammalian clades, and only recently has 3D imaging made morphological analysis possible (Van Valkenburgh et al, 2004; Rowe et al, 2005; Smith et al, 2011; Eiting et al, 2015), and shown that they preserve phylogenetic (Macrini, 2012) and ecological (Van Valkenburgh et al, 2011) signals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The architecture of the turbinals and floor of the nasal capsule determines whether orthonasal and/or retronasal air currents pass directly over olfactory epithelium. Turbinals are highly variable between mammalian clades, and only recently has 3D imaging made morphological analysis possible (Van Valkenburgh et al, 2004; Rowe et al, 2005; Smith et al, 2011; Eiting et al, 2015), and shown that they preserve phylogenetic (Macrini, 2012) and ecological (Van Valkenburgh et al, 2011) signals.…”
Section: Resultsmentioning
confidence: 99%
“…They lie directly in the stream of ortho-retronasal airflow and function in metabolic heat and water balance (Smith et al, 2011; Eiting et al, 2015). Saturation of air within the nose may also play a role in volatilization, but experimental airflow studies are still in their infancy.…”
Section: Resultsmentioning
confidence: 99%
“…During sniffing in dogs, air is inhaled from the front and exhaled to the side, which alters airflow rates and permits more efficient sampling of odorants [72]. Interestingly, bats appear to be different from rodents and dogs in that some air may pass through the olfactory recess during both inhalation and exhalation, thus potentially increasing odorant absorption on olfactory epithelium [73]. In addition to differences in width and size, bats also display considerable variation in shape and orientation of external nares (Fig 1).…”
Section: Discussionmentioning
confidence: 99%
“…As previously stated, the relationship between turbinal morphology and distribution of olfactory and respiratory epithelia within the nasal fossa differs among mammals, but is still poorly understood. Computational fluid dynamics studies informed by histology have been used to infer respiratory and olfactory performance in other mammals, including some bats, (Craven et al, ; Lawson et al, ; Eiting et al, ; Ranslow et al, ; Eiting et al, ; Pang et al, ; Xi et al, ), diffusible iodine‐enhanced CT scanning now allows nondestructive imaging of soft tissues (Gignac and Kley, ), and our understanding of the mammalian olfactory genome is rapidly improving (e.g., Hayden et al, ). Continued integrative work in these areas in an increasingly diverse sample of mammals will undoubtedly aid our understanding of how differences in olfactory, thermoregulatory, and osmoregulatory abilities are reflected in nasal fossa morphology.…”
Section: Discussionmentioning
confidence: 99%
“…However these types of studies remain rare due to the destructive nature of histology. Application of computational fluid dynamics (CFD) methods to model olfactory airflow within the mammalian nasal fossa suggests that the configuration of the turbinals and nasal fossa are important in determining the velocity and direction of olfactory airflow and patterns of odorant deposition (Craven et al, ; Lawson et al, ; Eiting et al, ; Ranslow et al, ; Eiting et al, ; Xi et al, , Pang et al, ).…”
Section: Introductionmentioning
confidence: 99%